Application of a negative thermal expansion oxide in SOFC cathode. Issue 1 (1st January 2021) - Lu, Fei; Yang, Mengjie; Shi, Yunjia; Wu, Changhui; Jia, Xusheng; He, Hao; Su, Jinrui; Chao, Mingju; Cai, Bin
Abstract: To improve the performance of solid oxide fuel cells (SOFCs) at intermediate temperature, an idea of adding a negative thermal expansion (NTE) oxide into cathode is proposed. The effects of NdMnO3-δ (NM) NTE oxide addition in Ba0.5 Sr0.5 FeO3-δ (BSF) cathode on the performance of proton-conducting SOFCs (H-SOFCs) are studied. The 30 wt % NM addition can lead to an ideal thermal matching between BSF-NM cathode and BaZr0.1 Ce0.7 Y0.2 O3-δ (BZCY) electrolyte, and improve the electrochemical performance of H-SOFCs significantly. At 500–750 °C, the peak power density (PPD) of H-SOFCs with BSF-NM cathode is 139–941 mW cm −2, which is apparently higher than that (73–661 mW cm −2 ) with BSF one. In addition, the relative increment of peak power density (PPD) increases from 42.36% at 750 °C to 90.41% at 500 °C, which is seldom obtained by conventional cathode doping. Comprehensive results of electrochemical impedance spectra, electrical conductivities, and SEM observations show that the apparent improvement of PPDs should be mainly associated with the increased three phase boundary length due to the ideal thermal matching between cathodes and electrolytes. In all, it provides a novel idea to develop intermediate and low temperature SOFCs. Highlights: An idea of adding a NTE oxide into SOFC cathode is proposed. Performance improvement of H-SOFCs at 500–750 °C is obtained by NM addition. An ideal thermal matching is obtained by 30 wt % NM addition. Performance improvement should be caused by the increased TPB length.